2015
DOI: 10.1371/journal.pone.0135433
|View full text |Cite
|
Sign up to set email alerts
|

Active Video Game Exercise Training Improves the Clinical Control of Asthma in Children: Randomized Controlled Trial

Abstract: ObjectiveThe aim of the present study was to determine whether aerobic exercise involving an active video game system improved asthma control, airway inflammation and exercise capacity in children with moderate to severe asthma.DesignA randomized, controlled, single-blinded clinical trial was carried out. Thirty-six children with moderate to severe asthma were randomly allocated to either a video game group (VGG; N = 20) or a treadmill group (TG; n = 16). Both groups completed an eight-week supervised program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(112 citation statements)
references
References 47 publications
1
106
0
5
Order By: Relevance
“…Sample sizes ranged from a small observational study of 7 to larger studies with 40 participants (parallel-groups design), 30 participants (crossover-trial) and 32 participants (observational study [28,58,61]. Only one study reported the testing of custom-designed hardware and games for respiratory conditions [55].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample sizes ranged from a small observational study of 7 to larger studies with 40 participants (parallel-groups design), 30 participants (crossover-trial) and 32 participants (observational study [28,58,61]. Only one study reported the testing of custom-designed hardware and games for respiratory conditions [55].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four of 12 included studies reported randomised studies examining the longer-term effects of AVGs versus traditional training in respiratory conditions [55,57,61,63]. One examined the effect of AVGs versus treadmill training in asthma, with training sessions twice a week over eight weeks [61].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations